КЛИНИКО-ГЕМОДИНАМИЧЕСКАЯ ХАРАКТЕРИСТИКА ЭФФЕКТИВНОСТИ ЭРАДИКАЦИОННОЙ ТЕРАПИИ У БОЛЬНЫХ С СОЧЕТАНИЕМ ИШЕМИЧЕСКОЙ БОЛЕЗНИ СЕРДЦА И ЯЗВЕННОЙ БОЛЕЗНИ - Ж. Г. Симонова; А. К. Мартусевич; Е. И. Тарловская (SINAPS LLC, 2014)
The aim of this work is investigation of H. pylori eradication on heart structural and geometry parameters and myocardial function at patients with coronary artery disease (CAD) and gastroenterological pathology. We studied 147 patients with CAD and gastroenterological pathology. It was stated, that H. pylori infection causes negative effect on intracardial hemodynamics and myocardial function at patients with combined pathology. We also fixed, that helicobaceriosis led to more clear myocardium remodeling and finally to cardiac insufficiency. It was shown, that eradication therapy optimized CAD symptoms by intracardial hemodynamics normalization.